Implementasi Penanaman Pemahaman Literasi Keagamaan di Lingkungan Sekolah Dasar - Cucu Darojatun Ajria; Amirudin Amirudin; Iqbal Amar Muzaki (UIN Fatmawati Sukarno Bengkulu, 2024)
Literacy is one of the challenges in Indonesia. Statistics show that 71% of the 34 provinces in Indonesia have a low literacy rate. Recently, another form of literacy has emerged, known as religion, which is believed to be a powerful model for facing the challenges of the 21st century. Literacy is a form of reading and writing that aims to improve religious understanding. Many researchers say that literacy, especially in elementary schools, often not taken into account by researchers. With that, this researcher strengthens students' religious literacy through digital media, the material presented is the casting of fairy tale videos. In this learning, it will be the attraction of children in the government; and can improve children in religious understanding without having to look at the guidebook. In this literacy media, it is also able to strengthen students' religious literacy by mastering the exemplary stories of prophets and applications This example in the context of his daily life.